AI Narratives in Indonesian Online Media: a Corpus Approach to Framing Analysis - Rossalyn Asmarantika (Universitas Multimedia Nusantara, 2025)
With an emphasis toward two popular Indonesian news websites, Kompas.com and Detik.com, this study aims to find out how artificial intelligence (AI) is framed within the framework of Indonesian online news media. This study uses AntConc linguistic analysis tools to do a corpus study on 88 news articles about artificial intelligence in order to expose the linguistic patterns and framing present in the selected news items. The results expose the opposing hopeful and cautions stories the media presents when interacting with artificial intelligence. The positive viewpoints underline how artificial intelligence can boost the healthcare industry, inspire creativity, and raise educational results among other things. These optimistic points of view highlight how important artificial intelligence is in helping to maximize daily activities. Conversely, the cautionary stories presented by critics highlight the major restrictions and possible risks connected to artificial intelligence, including the worrisome possibility of job displacement for many workers, urgent issues about data privacy that compromise personal confidentiality, and ethical conundrums resulting from the application of intelligent systems. These crucial factors remind the audience of the several difficulties and complex issues that are intrinsically related with the acceptance and integration of such transforming technologies into our countries.